COMMUNICATION STRATEGIES IN BUILDING PUBLIC TRUST BASED ON CYBER PUBLIC RELATIONS - Bahri, Saiful; Firdaus, Sulton; Wijaya, Muallim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In the digital era, where information is disseminated quickly through online platforms, the role of Cyber Public Relations (CPR) becomes very important in shaping public perception and trust. This study explores effective communication strategies used in building trust in online communities. Utilizing a qualitative research approach, this study examines various CPR techniques and their impact on building and maintaining trust among digital audiences. This research explores the integration of traditional public relations principles with digital communication tools to cultivate a positive online reputation. Emphasis is placed on transparency, authenticity, and responsiveness as core elements in building trust in cyberspace. Case studies and real-world examples illustrate successful CPR campaigns that have effectively fostered trust across diverse online communities. The use of communication strategies in cyber public relations does not experience significant differences, but places more emphasis on the use of communication technology which can provide efficiency in the community's communication experience, such as a sense of connection between the community and the institution. So it can be said that cyber public relations is a public relations strategy that cannot be ignored. As a strategy, cyber public relations certainly has an important role in shaping the image of an institution. The case study in this research is in-depth research about an individual, a group, an organization, an activity program, and so on at a certain time. The data collection technique in this research was carried out circularly using two approaches, namely; role observation (participant observation) and in-depth interviews (in-depth interviews). Meanwhile, data analysis in this research was carried out through; data reduction, data presentation, and drawing conclusions or verification. This research describes the implementation of several problem solving procedures studied by presenting data about communication systems using cyber public relations methods in increasing public trust in Madrasah Aliyah Nurul Jadid, so that the object of the problem can be clearly exposed. The object of research is communication carried out by Madrasah Aliyah Nurul Jadid, where communication using cyber public relations methods functions as persuasive communication to the community. These findings contribute to existing knowledge about Cyber Public Relations and offer practical insights for practitioners, scholars, and organizations seeking to improve their online communications strategies. As the digital era continues to shape the way information is consumed and shared, this research underscores the importance of ethical, transparent, and engaging communication in building trustworthy relationships between entities and the online public. Promotion and education through cyber public relations is expected to improve institutions and society, especially information about institutions, because it is assisted by information technology which is developing increasingly rapidly. By increasing understanding of teachers and the community, institutional development efforts can be carried out more easily. Apart from that, this institution also needs to be introduced regionally and globally to attract the interest of students and the public.